Inflation persistence revisited - Marika Karanassou; Dennis J. Snower (Queen Mary University of London, Department of Economics, 2004)
It is commonly asserted that inflation is a jump variable in the New Keynesian Phillips curve, and thus wage-price inertia does not imply inflation inertia. We show that this "inflation flexibility proposition" is highly misleading, relying on the assumption that real variables are exogenous. In a general equilibrium setting (in which real variables not only affect inflation, but are also influenced by it) the phenomenon of inflation inertia re-emerges. Under plausible parameter values, high degrees of inflation persistence (prolonged after-effects of inflation in response to temporary money growth shocks) and under-responsiveness (prolonged effects in response to permanent shocks) can arise in the context of standard wage-price staggering models.
Keywords: E31; E63; E42; E32; 330; Inflation persistence; Wage-price staggering; New Keynesian Phillips curve; Nominal inertia; Monetary policy; Forward-looking expectations; Inflation; Ungleichgewichtstheorie; Phillips-Kurve; Theorie